Animals in Circuses. Overview about the legal situation in Germany - Julia Havenstein (Universitat Autonoma de Barcelona. Facultat de Dret, 2017)
The European Union does not offer any legal framework for the protection of animals kept in circuses that would apply in Germany and the national provisions are too feeble to guarantee sufficient protection for animals kept in circuses. Furthermore, different from many other EU Member States, Germany does not prohibit or limit the use of wild animals in circuses. This is in spite of the fact that the majority of Germans are against exhibiting wild animals in circuses. Therefore, many Germany municipalities find their own ways to avoid circuses with wild animals in their territories.